Integrating Islamic and Muhammadiyah Values into Learning to Strengthen Character Development in Muhammadiyah Vocational Schools in Salaman - Safitri, Novita Aristawati; Khasanah, Safiratul; Purnomo, (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2025)
The primary challenge facing vocational education in Indonesia today extends beyond the acquisition of technical skills to include the urgent need for character formation, which is increasingly threatened by the forces of globalization and moral decline. This reality underscores the importance of a pedagogical approach that deliberately integrates Islamic and Muhammadiyah values into the educational process. This study aims to describe and analyze an integrated instructional model grounded in these values as a strategic framework for strengthening students' character at Muhammadiyah Vocational School in Salaman. Adopting a qualitative methodology with a case study design, data were collected through participatory observation, in-depth interviews, and document analysis to obtain a holistic understanding. The findings reveal that the integration of Islamic and Muhammadiyah values significantly enhances students’ discipline, sense of responsibility, and spiritual awareness. The model is structured around five key components: monotheism (tauhid), a thematic-integrative curriculum, reflective-participatory learning methods, a holistic character evaluation system, and strong institutional support. The comprehensive integration of these values proves to be an effective strategy for fostering sustainable character development in vocational education. Future studies are encouraged to examine the long-term impact of this model through longitudinal research and to explore the potential of digital technologies in advancing value-based character education. Abstrak: Tantangan utama pendidikan kejuruan di Indonesia saat ini bukan hanya berkutat pada penguasaan keterampilan teknis, tetapi juga pada persoalan pembentukan karakter siswa yang tergerus oleh arus globalisasi dan degradasi moral. Fenomena ini menuntut adanya pendekatan pembelajaran yang mengintegrasikan nilai-nilai keislaman dan keorganisasian secara sistematis dalam proses pendidikan. Studi ini bertujuan untuk mendeskripsikan dan menganalisis model pembelajaran terintegrasi berbasis nilai-nilai Islam dan Kemuhammadiyahan sebagai strategi penguatan karakter siswa di Muhammadiyah Vocational Schools Salaman. Penelitian dikaji menggunakan pendekatan kualitatif dengan desain studi kasus, melalui teknik observasi partisipatif, wawancara mendalam, serta telaah dokumen untuk memperoleh data secara komprehensif. Riset menemukan bahwa penerapan integrasi nilai Islam dan Kemuhammadiyahan mampu membentuk sikap disiplin, tanggung jawab, dan memantik kesadaran spiritual siswa. Model integrasi mencakup lima komponen utama yaitu ketauhidan, struktur kurikulum tematik-integratif, metode reflektif-partisipatif, sistem evaluasi karakter holistik, dan dukungan institusional. Integrasi menyeluruh nilai Islam dan Kemuhammadiyahan terbukti menjadi pendekatan strategis yang efektif untuk memperkuat karakter siswa SMK secara berkelanjutan. Penelitian lanjutan disarankan untuk mengevaluasi efektivitas jangka panjang model ini melalui studi longitudinal dan eksplorasi pemanfaatan teknologi digital dalam penguatan pendidikan karakter berbasis nilai Islam.